Dukungan Perpustakaan Khusus Instransi Pemerintah Menunjang Kinerja Pejabat Pengelola Informasi dan Dokumentasi - Ceria Isra Ningtyas; Ashry Noviana Fajry; Dhian Deliani (Jurnal IPI (Ikatan Pustakawan Indonesia), 2020)
Public information organization and services are the main activities of the Chief of Information and Documentation Officer (PPID). In this case, the library unit has a function as a supporting process of PPIDs’ activities in an institution. This supporting process cannot be separated from the perception of the head of the libaries in terms of library supports in supporting PPIDs’ performances. This study attempts to find out the perception of the head of the libraries in terms of library supports to PPIDs’ performance. The purpose of this study (1) to explore library supports for the PPIDs’ performance and (2) to explain the obstacles of the library leaders in developing those supports. There are seven aspects of supports exploring in this study, which are: Knowledge, Coordination, Public information organization, PPIDs’ service, budget allocation, information system development and reporting. This study developed using qualitative methods by interviewing 16 informants who are the leaders of the government libraries. The results of this study are: (1) in general, library unit supports for the PPIDs’ performance based on the perception of heads/library leaders is still low. There is only one aspect, which is Knowledge that shows as high. Other six aspects are still in medium and low category. The barriers faced by the heads/library leaders in supproting PPID are the lack of synergy between the PPID unit and the library unit, and the lack of regulatory supports from the head of the institutions.